2023
DOI: 10.1021/acs.inorgchem.3c00546
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Insights on the Complexation of Americium(III) and Europium(III) with Diglycolamide- and Dimethylacetamide-Functionalized Calix[4]arenes

Abstract: Separation of minor actinides from lanthanides is one of the biggest challenges in spent fuel reprocessing due to the similar physicochemical properties of trivalent lanthanides (Ln­(III)) and actinides (An­(III)). Therefore, developing ligands with excellent extraction and separation performance is essential at present. As an excellent pre-organization platform, calixarene has received more attention on Ln­(III)/An­(III) separation. In this work, we systematically explored the complexation behaviors of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Researchers have developed the ligands utilizing the principle of hard–soft acid–base for the separation of An­(III) and Ln­(III). Diamide ligand-based extractants, where the presence of nitrogen provides softness, are used for the separation of An­(III) and Ln­(III). Hydroxycarboxylic acids, namely, α-hydroxyisobutyric acid (HIBA) and mandelic acid (MA) (Scheme ), have been well-known eluting reagents for the liquid chromatographic separation of actinides and lanthanides. Reports showed that the elution pattern changes in order by the application of HIBA instead of MA and vice versa. Both HIBA and MA bind the metal ions through the same functional moieties but differ in their side-chains.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have developed the ligands utilizing the principle of hard–soft acid–base for the separation of An­(III) and Ln­(III). Diamide ligand-based extractants, where the presence of nitrogen provides softness, are used for the separation of An­(III) and Ln­(III). Hydroxycarboxylic acids, namely, α-hydroxyisobutyric acid (HIBA) and mandelic acid (MA) (Scheme ), have been well-known eluting reagents for the liquid chromatographic separation of actinides and lanthanides. Reports showed that the elution pattern changes in order by the application of HIBA instead of MA and vice versa. Both HIBA and MA bind the metal ions through the same functional moieties but differ in their side-chains.…”
Section: Introductionmentioning
confidence: 99%
“…[10] The coordination chemistry of doubly [11,12] and quadruply substituted calix [4]arenes has been extensively investigated. [13][14][15][16][17] Much less is known about the lanthanide coordination chemistry of singly [18] or triply [19] functionalized calix [4]arenes, presumably due to more complicated synthetic procedures.…”
Section: Introductionmentioning
confidence: 99%